HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN DAYA TAHAN DENGAN HASIL KETEPATAN MENENDANG DALAM PERMAINAN SEPAK BOLA ATLET PPLP RIAU - Alfi, Zulmardian; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations on the Riau pplp soccer athlete, the researchers saw a number of problems, namely the low ability of athletes to place kicks if they had played over 30 minutes. Besides that, the kick strength they showed was still weak when it was over 30 minutes. Athletes very often make mistakes when playing long enough. Opportunities in the author's view were lost due to the condition of endurance and explosive weak leg muscles. Kick placement is needed but must also be followed by endurance and explosive ability of leg muscles so that the resulting kick can be right on target and fast. From the results of this study, it is known that there is a relationship between leg muscle power and accuracy of soccer game shooting in the PPLP Dispora Riau team, where the value of the calculation is 0.629. From the table of r values obtained rtable value at df = 18 with a significant level (α) 0.05 = 0.444. This means that the value of r count is 0.629> r table (0.444). The results of the correlation calculation obtained a calculated value of 0.496. From the table of r values obtained rtable value at df = 18 with a significant level (α) 0.05 = 0.444. This means that the value of rhitung is 0.496> rable (0.444), meaning that the hypothesis is accepted and there is a relationship between springs and akurasishooting in football games on the PPLP Dispora Riau team.Key Words: Explosive Power, endurance, Football Accuracy